Genetic neurocognitive profile of autism unveiled with gene transcription - Yingxing Zhang; Fangfang Li; Hongli Wu; Wei Du; Jianhua Shu; Anqing Wang; Chunsheng Xu; Chuanfu Li; Ya Wang; Sheng Hu (Neurobiology of Disease)
How neurocognitive processes elaborate phenotypic heterogeneity within autism spectrum disorder (ASD) remains unknown. Applying the principal component analysis to the Neurosynth database, we established neurocognitive profiles to characterize the phenotypic heterogeneity of ASD, revealing a cortical hierarchical axis that separates the temporal cortex from other networks. By integrating neurocognitive profiles with transcriptomic data, we found that gene sets shaping the patterns of neurocognitive profiles are enriched in ASD-related biological processes and ASD pathogenic risk. Using a data-driven approach, we identified a topographic network for ASD, comprising the temporal, frontal, somatosensory, and visual cortices, with its transcriptomic signatures differentiating between regions over neurodevelopment. Additionally, functional reorganization in ASD within the topographic network has occurred with the temporal cortex as the central node. Collectively, our results reveal spatially covarying transcriptomic and neurocognitive profiles, emphasizing the influence of functional reorganization and its underlying genetic mechanism on phenotypic heterogeneity in ASD.